Procedural sedation in dentistry with the use of dexmedetomidine: effects on clinical examples (Pain medicine, 2023)
The presence of acute pain can be the worst negative impressions of a person. Therefore, it is necessary to ensure the control of acute pain for comfort and prevention of the formation of chronic pain syndrome intraoperatively. The development of a multimodal approach to the control of acute pain allows for shorter results. The more we use antinociceptive receptors for pain control, the more comfortable our patient feels. Alpha-2-adrenergic agonists (clonidine, dexmedetomidine) became a key part of the anesthesiologist’s recruitment in the perioperative period. The very selective infusion of dexmedetomidine on alpha-2a central and peripheral receptors and alpha-2c receptors allowed the drug to be more widely absorbed during procedural sedation. The need for more drugs for procedural sedation may be taken to the maximum possible comfort for the patient, the happy doctor and the anesthesiological team, the change in drug administration and the most likely awakening. To balance and satisfy the needs of the consumer to help the most practical way to achieve the goal of combinations of drugs and analysis of useful and negative effects.Special notice. There are presented two cases with typical development but different in terms of surgical applications of clinical manifestations of the described effects, associated with the intake of Kvanadex (dexmedetomidine hydrochloride) during procedural sedation in outpatient dentistry.Conclusions. The administration of dexmedetomidine (Kvanadex) intraoperatively together with propofol during procedural sedation in outpatient dentistry allows to control the pain in the perioperative period with vicarious treatment of basic traditional drugs (acetaminophen, NSAIDs) in non-healing doses, changing the dose of propofol during the procedure, reducing the vomit reflex, allowing for a comfortable follow-up of the doctor’s commands (surgeon, implantologist, orthopedist) and more rapid transfer of the patient to the awakening ward.
Keywords: procedural sedation; dexmedetomidine; outpatient dentistry